Enhancing Workplace Road Safety through the Work-Related Road Safety Support Program - Bakar, Harun; Rusli, Rusdi; Adinegoro, Yusuf; Baharudin, Mohd Rafee (Environment-Behaviour Proceedings Journal, 2025)
Work-related road safety is a critical concern in Malaysia, with crashes affecting employee welfare and organizational performance. This study evaluates the effectiveness of the Work-Related Road Safety Support Program (WRRSP) in 40 organizations, comprising 20 with the intervention and 20 without. The program, delivered through expert consultations and tailored recommendations, aimed to strengthen management practices and reduce risks. Using a pre- and post-program questionnaire and univariate general linear model analysis, significant improvements were observed in safety management, communication, and employee induction among intervention organizations, confirming the positive impact of WRRSP in enhancing workplace road safety.